Considerations, possible contraindications, and potential mechanisms for deleterious effect in recreational and athletic use of selective androgen receptor modulators (SARMs) in lieu of anabolic androgenic steroids: A narrative review - Machek, Steven B.; Cardaci, Thomas D.; Wilburn, Dylan T.; Willoughby, Darryn S. (Steroids, 2020)
[Display omitted] •SARM’s were developed to provide clinical androgen benefits without side effects.•SARMs are becoming more common in recreational abuse.•SARMs were recently FDA banned and lack supporting evidence.•SARMs may impact hypothalamic-pituitary regulation with systemic ramifications. Anabolic androgenic steroids (AAS) are testosterone and testosterone-derivative compounds sporadically employed by athletes and increasingly used recreationally to acquire a competitive edge or improve body composition. Nevertheless, users are subject to undesired side effects majorly associated with tissue-specific androgen receptor (AR) binding-mediated actions. More recently, selective AR modulators (SARMs) have gained popularity towards delivering androgen-associated anabolic actions with hopes of minimal androgenic effects. While several SARMs are in preclinical and clinical phases intended for demographics subject to hypogonadism, muscle wasting, and osteoporosis, several athletic organizations and drug testing affiliates have realized the increasingly widespread use of SARMs amongst competitors and have subsequently banned their use. Furthermore, recreational users are haphazardly acquiring these compounds from the internet and consuming doses several times greater than empirically reported. Unfortunately, online sources are rife with potential contamination, despite a prevailing public opinion suggesting SARMs are innocuous AAS alternatives. Considering each agent has a broad range of supporting evidence in both human and non-human models, it is important to comprehensively evaluate the current literature on commercially available SARMs to gain better understanding of their efficacy and if they can truly be considered a safer AAS alternative. Therefore, the purpose of this review is to discuss the current evidence regarding AAS and SARM mechanisms of action, demonstrate the efficacy of several prominent SARMs in a variety of scientific trials, and theorize on the wide-ranging contraindications and potential deleterious effects, as well as potential future directions regarding acute and chronic SARM use across a broad range of demographics.